2003
DOI: 10.1115/1.1524584
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Turbulence Model Influence on the Numerical Simulations of Unsteady Cavitation

Abstract: Unsteady cavitation in a Venturi-type section was simulated by two-dimensional computations of viscous, compressible, and turbulent cavitating flows. The numerical model used an implicit finite volume scheme (based on the SIMPLE algorithm) to solve Reynolds-averaged Navier-Stokes equations, associated with a barotropic vapor/liquid state law that strongly links the density variations to the pressure evolution. To simulate turbulence effects on cavitating flows, four different models were implemented (standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(186 citation statements)
references
References 8 publications
6
164
1
5
Order By: Relevance
“…RANS turbulence models have been used to simulate various industrial fluid machines for years because of their good performance in giving acceptable simulation results within a reasonable computational time. For cavitating flow simulations, recent CFD studies showed that these turbulence models would need some modifications in the turbulent eddy viscosity [31,33,34]. There are several different RANS turbulence models for different utilities.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…RANS turbulence models have been used to simulate various industrial fluid machines for years because of their good performance in giving acceptable simulation results within a reasonable computational time. For cavitating flow simulations, recent CFD studies showed that these turbulence models would need some modifications in the turbulent eddy viscosity [31,33,34]. There are several different RANS turbulence models for different utilities.…”
Section: State Of the Artmentioning
confidence: 99%
“…To improve numerical simulations by taking into account the influence of the local compressibility effect of two-phase mixtures on turbulent closure models, Coutier-Delgosha [33] proposed to reduce the mixture turbulent viscosity of fluid at vapor/liquid interfaces based on the local vapor volume fraction α v by substituting μ T in eq. (3) with μ T_mod :…”
Section: 4mentioning
confidence: 99%
“…However, in high speed cavitating water jets bubble clouds oscillates intensively and the eddy viscosity in a local area of bubble cloud may be greatly absorbed. In order to capture the unsteadily shedding of bubble clouds a density modification is introduced and then the eddy viscosity is evaluated by the following formula [10,15].…”
Section: Governing Equations For Turbulent Cavitating Flowmentioning
confidence: 99%
“…During the execution of the strategy of diagnosis, the measurable signals can provide significant information, on the defects appearance to facilitate the determination of the supervision parameters, representing the defects signatures, their degree and persistence. From these parameters, the decisional system can conceive powerful diagnosis approach [1][2][3]. To realise this prospect, we proposes in this work to examine and illustrate the application ability of the spectral analysis approach, in the area of fault detection and isolation industrial systems.…”
Section: Introductionmentioning
confidence: 99%